Shutdown of an offshore wind power plant without using a brake to meet the required ramp rate in various storm-driven conditions. (15th March 2015) - Kim, Y.H.; Kim, J.H.; Kang, Y.C.; Lee, B.J.; Anaya-Lara, O.; Burt, G.; O'Malley, M.J.
Abstract: This paper proposes an offshore WPP (wind power plant) shutdown algorithm that does not use a braking system and meets the required ramp rate in the grid code in various storm-driven conditions. The proposed algorithm determines the number of WGs (wind generators) to shut down simultaneously to achieve this requirement without using brakes. Based on the storm speed and direction measured at a WM (wind mast) installed several kilometers away from the WPP, the storm-arrival time from the WM to each WG is calculated. Then, an arrival-ordered sequence is generated for the WGs based on these storm-arrival times. The WGs are grouped in a predetermined number to shut down simultaneously. The shutdown start- and end-times of the WGs are determined by considering the storm-arrival time and the shutdown duration time. The algorithm re-calculates the storm-arrival times and the shutdown start- and end-times of the WGs if the storm speed and/or direction change. The various test results demonstrate that the algorithm successfully shuts down the WPP without using a brake by meeting the required ramp rate even when the storm speed and direction change. Highlights: We propose an offshore WPP shutdown algorithm that does not use a braking system. The algorithm determines the number of wind generators to shut down simultaneously. The shutdown start- and end-times of wind generators are determined. The algorithm re-calculates the storm-arrival times if the storm condition changes. The algorithm shuts down a WPP by meeting the ramp rate in various storm conditions.